2005
DOI: 10.2514/1.8177
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Wake-Vortex Parameters Measured by Pulsed and Continuous-Wave Lidars

Abstract: Field trials carried out at Tarbes airfield in the summer of 2002 offered the unique opportunity to compare the results of simultaneous wake-vortex measurements by the 2-µm pulsed Doppler lidar from DLR, German Aerospace Research Center, and the 10-µm continuous wave (cw) Doppler lidars from ONERA and QinetiQ. The discrepancies in vortex core position obtained from the data of the pulsed lidar and the cw lidars are 9 m for the vertical and 13 m for the horizontal coordinates. The accuracies of the vortex circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 26 publications
0
21
0
1
Order By: Relevance
“…They point out that to date lidar seems to be the only technology capable of operating reliably under most meteorological conditions but not in fog or heavy rain [although the radar-acoustic method of Rubin (2000) shows promise in these conditions]. Recent results of Frehlich and Sharman (2005) and Köpp et al (2005) show that vortex positions between CW lidars and pulsed lidars show differences of 9 and 13 m for the vertical and horizontal components, respectively. The accuracy of the lidar-based estimates of vortex circulation is given as 13 m 2 s Ϫ1 .…”
Section: Introductionmentioning
confidence: 92%
“…They point out that to date lidar seems to be the only technology capable of operating reliably under most meteorological conditions but not in fog or heavy rain [although the radar-acoustic method of Rubin (2000) shows promise in these conditions]. Recent results of Frehlich and Sharman (2005) and Köpp et al (2005) show that vortex positions between CW lidars and pulsed lidars show differences of 9 and 13 m for the vertical and horizontal components, respectively. The accuracy of the lidar-based estimates of vortex circulation is given as 13 m 2 s Ϫ1 .…”
Section: Introductionmentioning
confidence: 92%
“…Körner and Holzäpfel [84] analyzed 8052 aircraft landings recorded by Doppler LiDARs at several international airports, concluding that 3.7% of the landing vortices were generated below 50 m. To artificially accelerate wake vortex decay or destruct wake vortices for the purpose of aviation safety, it is crucial to uncover the physical mechanism of wake vortex decay, particularly during landing phase and the touchdown process. LiDAR observations indicated that continuous vortex decay was associated with strong turbulence [85] while the two-phase decay, i.e., an initial phase of moderate decay followed by a phase of rapid decay, occurred in weakly turbulence environments [86], corroborating the vortex evolution found in corresponding CFD simulations [87]. With the help of LiDAR measurements, it was found that the radii of vortex cores were almost constant during the decay process [88] and this process could be accelerated by ground effects [75].…”
Section: Aircraft Wake Vortexmentioning
confidence: 99%
“…Hence, the initial condition uncertainty is taken into account by adding a priori determined standard deviations to the REA uncertainty limits. For WakeMUC, the initial conditions are derived from lidar measurements, so the uncertainties are the lidar measurement uncertainties σ z0 = 9 m, σ y0 = 13 m, and σ Γ0 = 13 m 2 /s (Köpp et al 2005). If not derived from lidar, the uncertainty for  0 is calculated using the error propagation method considering uncertainties of aircraft mass, air density, and flight speed (σ z =3 m and σ y =7 m (Holzäpfel 2014), σ m =1300 kg, σ b =1.5 m, σ ρ =0.0048 kg/m 3 , σ v =4 m/s).…”
Section: Applicationmentioning
confidence: 99%